France and European macroeconomic policy coordination: from the Treaty of Rome to the euro area sovereign debt crisis. (3rd April 2017) - Howarth, David; Schild, Joachim
Abstract: French support for European (EC/EU)-level macroeconomic policy coordination has been driven by remarkably consistent preferences since the 1950s. With the exception of the de Gaulle decade (1958–1968), French governments have sought European-level mechanisms for balance of payments support. This article sets out to explain these remarkably stable French preferences on European-level macroeconomic policy coordination over time through a combination of an interest-based analysis referring to structural and competitive weaknesses of the French economy and an ideational explanatory analysis focused upon French Keynesian thinking on symmetrical adjustment of both deficit and surplus countries. French preferences align largely with the concept of 'embedded liberalism'. This article also interprets a number of developments in EU-level economic governance in response to the banking and sovereign debt crises that provided a policy window for France to move European-level mechanisms and institutions towards long-held French preferences.